OPTIMALISASI HIGIENITAS PADA UMKM DI KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Sri Widiyastuti; Tiza Yaniza; Rachmawati Rachmawati; Dina Karlina; Siti Rohani; Uti Asikin (Jurnal Abdimas Bina Bangsa, 2024)
The lack of partner knowledge regarding packaging, labels and hygiene that partners need to pay attention to makes the implementation team feel they have to provide education regarding matters regarding hygiene to partners and the surrounding community. The method of implementing activities is legal counseling and technical training on product packaging in accordance with statutory provisions as well as increasing the production capacity of household businesses. The obligation to meet food packaging standards in order to create safe food products is closely related to food labeling obligations. This PKM activity is an effort to empower MSME business actors in food production. So that MSME business actors can produce and package food according to food packaging and labeling standards, they are provided with training on packaging and making food labels that comply with regulations. Apart from that, MSME players are also given equipment assistance that can support and increase their production, but still taking into account statutory provisions. In the future, it is hoped that more MSME business actors will have legal awareness regarding food packaging and labels when carrying out their business activities